Injection effects on settling velocity - Le, Duc Anh (2015)
Settling is a process by which particulates that experience forces fall to the bottom of a liquid and form sediment at the vessel base. The terminal velocity or settling velocity of particle is an important parameter in sediment transport. The drag coefficient is also a crucial property in mechanics of particle motion, which is used to quantify the resistance of an object in a fluid environment, such as water. However limited studies were done on possible injection effect on drag coefficient and settling velocity of sediment particles. The objective of this experimental project were to investigate to what extent injection influences the settling velocity, drag coefficient as well as acceleration profile of a single sediment spherical particle, relative to that in quiescent condition. The laboratory experiments were conducted in a vertical water cylinder that was 100mm in diameter and 1100mm in height. Two uniform plastic spherical particles which are 6.11mm and 6.08mm in diameter were used. Different injection flow rates such as 2.5×10-5 m3/s, 5×10-5 m3/s, 7.5×10-5 m3/s, 1×10-4 m3/s were also used to calculate settling velocity and drag coefficient in injection condition. Overall, the results of this project provided evidence that injection has modified the drag coefficient as well as influenced settling velocity of particle. The injection is found to generate a large amount of drag and the higher injection intensity produced the higher drag or resistance in fluid, which causes lower terminal settling velocity. The acceleration profile or the length of acceleration zone is found to remain relatively consistent under injection effects.